Comparing cigarette-cue attentional bias between people with HIV/AIDS and people with opioid use disorder who smoke - Gopalkumar Rakesh; Joseph L. Alcorn; Rebika Khanal; Seth S. Himelhoch; Craig R. Rush (Health Psychology and Behavioral Medicine, 2023)
ABSTRACTBackground Special populations like people living with HIV/AIDS (PLWHA) and people with opioid use disorder (OUD) smoke tobacco cigarettes at rates three to four times greater than the general population. Patients with tobacco use disorder exhibit attentional bias (AB) for cigarette cues. Eye tracking can quantify this bias by measuring fixation time (FT) on cigarette and matched neutral cues, to calculate an AB score. Although previous studies have measured this bias in people who smoke without any other comorbid conditions, no study, to our knowledge, has measured or compared this bias in special populations.Methods We performed exploratory analyses on eye tracking data collected in two separate randomized clinical trials (RCTs) (NCT05049460, NCT05295953). We compared FT and cigarette-cue AB score (measured by subtracting FT on neutral cues from FT on cigarette cues) between PLWHA and people with OUD who smoke, using a visual probe task and Tobii Pro Fusion eye tracker. We used two cigarette cue types, one encompassing people smoking cigarettes and the other consisting of cigarette paraphernalia. We used two cue presentation times, 1000 and 2000 milliseconds (ms).Results Cues of people smoking cigarettes elicited greater AB than cues of cigarette paraphernalia across both subject groups when cues were presented for 2000 ms, but not 1000 ms. PLWHA who smoke exhibited greater AB for cues of people smoking cigarettes than cigarette paraphernalia when presented for 2000 ms compared to people with OUD who smoke.Conclusion We use cigarette-cue AB to quantify craving and cigarette consumption in two populations smoking at elevated rates. The addition of social cues potentiates cigarette cue AB, based on cue type and stimulus presentation time. Understanding the neurobiology of this relationship can help design novel smoking cessation treatments that target AB and prevent relapse in these populations with suboptimal response to smoking cessation treatments.Trial registration Clinical trials that provided the data for post hoc analyses are NCT05049460 and NCT05295953.